Improvement of human resources as a factor for increasing the teaching performance in pre-university education - Rus, Mihaela; Sandu, Mihaela Luminița; Caranfil Ianoș, Ionica; Enculescu, Claudia (Technium Social Sciences Journal, 2022)
People are a valuable resource, "the most valuable asset" (Maican, 2001), for any type of organization, regardless of the field of activity. The new philosophy of organisations places particular value on the role of human resources because: human resources are the organisation; people are a common resource and a key resource, a vital resource, today and tomorrow, of all organisations, which ensures their survival, development, and competitive success. A school organization that teaches is open and able to profit in a continuous self-renewal, through improvement, improvement that occurs through a continuous process of quality improvement, which increases the efficiency of the organization. Performance, in a school organization, depends largely on the quality of human resources. Lifelong learning is required both as a necessity and as a solution to the changes taking place in various areas of the life of the individual and society. The multiplication of the training needs of adults in general, of teachers in particular, is generated by a series of internal and external pressures. The purpose of this approach is to identify, synthesize, complete, explain the process of professionalization of human resources – increasing school performance within the organization, as a result of their improvement, in the context of permanent changes. Through the theoretical and methodological approach, we aimed to make a useful and relevant contribution to the existing practice, considering the investigative approach as representing the beginning of a process and not its end. From a theoretical point of view, we have followed the scientific substantiation of the human resources management, at the level of the school organization through the systematization and outlining of the epistemological, theoretical and methodological premises from the specialized literature; and from an investigative point of view, we carried out empirical research through which we wanted to contribute to the development of a reference framework in this field.